Hubungan Faktor Sosial Ekonomi dengan Kesehatan Mental pada Anak Korban Seksual di Provinsi Aceh - Nofita Yulandari; Radhiah Zakaria; M. Marthoenis; Hafnidar A. Rani; Asnawi Abdullah (Jurnal Kesehatan Komunitas, 2022)
Sexual violence against children will have an impact on the development of children's mental health and the case is like an iceberg phenomenon. this study examines the relationship between the socio-economic and mental health of child victims of sexual in Aceh Province, this type of analytic observational research uses a cross-sectional design, the population of children experiencing sexual violence is based on data from UPTD-PPA Aceh, Aceh Province in 12 districts, totaling 123 children, total population sample, the results showed that the factors associated with the development of mental health of children were the father's secondary education (OR = 3.6; p = 0.002), the father's basic education (OR = 2.8; p = 0.025), the father's occupation was self-employed (OR = 3.6; p=0.03), environmental influence (OR=2.7; p=0.009), family support was not supportive (OR=9; p=0.0001) and the counselor's behavior was not supportive (OR=2.3 ; p = 0.026), the results of the multivariate analysis concluded that children who experienced sexual abuse tend to experience abnormal mental health development 15 times greater than the other variables.